NERVE STRENGTH AND ITS RELATIONSHIP TO SPECIFIC MUSCLE STRENGTH AND THE PERFORMANCE OF FLOOR MOVEMENTS BY ARTISTIC GYMNASTS - Abduljabbar Aboob, Dr.Marwa (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
During the last decade, sports have witnessed significant and noticeable development in various sporting competitions, and this development is not a matter of coincidence or randomness, but rather has come as a result of great efforts, whether collective or individual, by those in charge of sports fields and competitions.Scientific research in the field of sports is one of the most important effective ways to develop players and sports in general. The game of gymnastics has relied on this research significantly and significantly. Among these researches is physiological research, which is largely concerned with the state of the body’s functional systems and the developments that occur in them. This study aimed to To identify the relationship between nerve strength, the special muscle strength, and the performance of floor movements for artistic gymnastics players, as well as to identify the nerve strength and the performance of floor movements for artistic gymnastics players. The researcher assumed that there is a significant correlation between nerve strength and the special muscle strength for female artistic gymnastics floor movements players. The researcher also assumed There is a significant correlation between nerve strength and the level of performance of ground movements.Hence the importance of this research through the importance of nerve strength, as we find it to be the primary influence on stimulating muscle fibers and thus producing special muscle strength in order to achieve a very high level of skill performance and strong and good achievement, which gives the research great benefit to coaches in codifying training loads and adjusting them to suit the player.The sample was chosen by the researcher in a deliberate manner, and her research sample was selected from the national team players from the artistic gymnastics and floor movements category (women), as the number of players was (4) and they represent the community of origin (100%), and (1) of the players was excluded. To conduct a reconnaissance experiment on it.